2001
DOI: 10.1111/1467-9507.00179
|View full text |Cite
|
Sign up to set email alerts
|

Children's Use and Knowledge of Display Rules for Anger Following Hypothetical Vignettes versus Following Live Peer Interaction

Abstract: Our primary goal was to examine the correspondence between children's self-reported use and knowledge of display rules for anger following hypothetical vignettes versus following live peer interactions. Our secondary goal was to investigate whether children's self-reported experience and self-reported expression of anger were related their observed anger expression, considered an observational measure of use of display rules for anger. Participants were 274 second-grade children. Children were first interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 57 publications
1
21
1
1
Order By: Relevance
“…The findings we have presented are important because they show that individual differences in feelings of anger, which are accessible to children, are associated with victimization and maladaptive responses in emotion eliciting contexts. Observational research has found that individual differences in the subjective experience of anger are not strongly associated with displays of emotion when one peer is provoking another [22,23]. The discrepancy with our findings, however, might be attributed to a restricted range in feelings of anger assessed in the laboratory studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings we have presented are important because they show that individual differences in feelings of anger, which are accessible to children, are associated with victimization and maladaptive responses in emotion eliciting contexts. Observational research has found that individual differences in the subjective experience of anger are not strongly associated with displays of emotion when one peer is provoking another [22,23]. The discrepancy with our findings, however, might be attributed to a restricted range in feelings of anger assessed in the laboratory studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Kochenderf-Ladd also found that young school-age victims were not angrier than non-victims but were more likely than non-victims to be motivated to seek revenge [20]. Among older children associations between subjective feelings and observable displays are weak to non-existent [21][22][23], although children with stronger motivation to maintain positive social interactions are less likely to display anger or aggression in response to provocation [24][25][26]. Taken together, the findings highlight the importance of examining motivation and feelings as indicators of subjective emotional experience and including a range of contexts in measures of emotion processes [27].…”
Section: Anger Managementmentioning
confidence: 95%
“…Studies that have examined aggression and not bullying have found that aggressive children are less likely to use display rules for anger than non-aggressive children (Underwood et al, 1992). Others have found rejected and aggressive second grade children are no different than their peers when using and understanding display rules in live or hypothetical situations (Parker et al, 2001). Our findings mirror those by suggesting that children who repeatedly aggress against the same children perform as well as their peers on measures of emotional display rule knowledge.…”
Section: Discussionsupporting
confidence: 78%
“…Researchers could compare selfreports with observations regarding children's emotion regulation in the context of peer relationships (e.g., McDowell, O'Neil, & Parke, 2000;Parker et al, 2001). Further, emotions such as being afraid or fearful, and mixed emotions such as feeling both sad and mad about the same situation, might be options as well as emotion intensity ratings.…”
Section: Future Directions and Limitationsmentioning
confidence: 99%